Literature Review: The Effect of Consumption Vigna radiata, Carica papaya, and Sauropus androgynous Leaves on Breast Milk Production - Pujiastuti, Nurul (Journal of Nursing Science Update (JNSU), 2022)
The lack of understanding about enhancing breast milk production is a challenge that many mothers confront after giving delivery. The hormones oxytocin and prolactin naturally affect breast milk release and production. To improve milk production, however, the production of these two hormones must be increased by consuming certain foods. This study aimed to gather and analyze articles about the effect of Vigna radiata, Carica papaya, and Sauropus androgynous leaves on breast milk production. The articles used in this literature review met specific criteria, such as publishing in a peer-reviewed journal from databases such as DOAJ, Science Direct, Copernicus, SINTA, ResearchGate, GARUDA, and Google Scholar. The articles were chosen based on their publication dates, ranging from 2015 to 2020. The PICOS framework is used to select articles chosen subsequently using the JBI Critical Appraisal tools. According to the article reports, ingesting Vigna radiata, Carica papaya, and Sauropus androgynous leaves influences breast milk production by stimulating the hormones oxytocin and prolactin, which can enhance breast cancer milk production. Suggestions for more research, particularly on the time and amount of Sauropus androgynous, Vigna radiata, and Carica papaya leaves given to postpartum moms to improve breast milk production.